MENINGKATKAN KEMAMPUAN BERPIKIR ILMIAH PESERTA DIDIK KELAS VIII MELALUI PEMBELAJARAN BERBASIS MASALAH MATERI ZAT ADITIF - Shefi Andarista; Laily Rosdiana (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
This research aimed to describe the improvement of students' scientific thinking skills on additive material using problem-based learning model implemented in one of public Junior High Schools in Surabaya. This research design used one-group pretest-posttest. This research involved 36 students of class VIII. This research's data collection methods included observation, tests, and questionnaires. The results showed that the implementation of problem-based learning got the average result from two meetings at 94.5% (very good). The average normalized gain for all students in the medium category. The average normalized gain of students in each sub-indicator of scientific thinking ability, namely: inquiry and analysis, increased in the high category, while inference and argumentation increased in the medium category. The students' responses to problem-based learning got very good results. Therefore, it can be concluded that problem-based learning can improve scientific thinking skills on additive material.